Humanity may Triumph over Heaven. Wang Tingxiang's Natural Philosophy in its Historical Context. (3rd July 2022) - Ahn, Kanghun
Abstract : This paper examines Wang Tingxiang's natural philosophy within its historical context. Wang left numerous accounts on natural phenomena in which he sought to discover the causes or hidden mechanisms of the processes he uncovered. To this end, he first had to radically deconstruct the so-called correlative thinking that perceives a fundamental connection between humanity and the natural world. Wang deemed this worldview a critical blockage of his scholarly aim and instead articulated his empirical stance as an alternative pathway. In this sense, he emphasized the sensory data gathered from direct observations as the only legitimate source of natural knowledge. With such data, aided by the human faculty of thinking, one could eventually uncover the principles that underpin natural phenomena. Further, it is crucial to understand why and in what context Wang proposed this empirical stance. To answer this question, I highlight the environmental crisis associated with the Little Ice Age that resulted in numerous natural disasters during Wang's time. In order then to overcome such disasters, Wang emphasized the accurate understanding of natural phenomena so that people could predict future outbreaks of such disasters, thereby preventing the (re)occurrence of potential harms. Although Wang's worldview enjoyed little to no popularity in his time, a similar empirical strand re-emerged and garnered greater attention as the environmental crisis grew more severe during the seventeenth century.